2021
DOI: 10.1021/acs.jafc.0c06533
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Study of Sorghum (Sorghum bicolor) to Interpret Plant Behavior under Variable Field Conditions in View of Smart Agriculture Applications

Abstract: To tackle the urgency of smarter crop management, the complex nature of agricultural ecosystems needs to be better understood, employing and combining different techniques and technologies. In this study, untargeted metabolomics and agrometeorological survey were coupled to study the variation of Sorghum bicolor (L.) Moench metabolome during crop development, in response to environmental and anthropic factors. Twelve crop fields in the Emilia-Romagna region, Italy, were monitored and sampled at different stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Additionally, FTIR spectroscopy enables high-throughput measurements [ 53 , 54 ], suggesting that it can be used for chemo-typing heat-stress responses in crop breeding programs. Easier setup of FTIR spectroscopic facilities in comparison to that of other metabolomic platforms may also be beneficial for applying this technology to field metabolome studies [ 55 , 56 ]. Recently, FTIR-based remote sensing technologies have emerged as a new tool for monitoring the surface properties of land [ 15 , 57 ], and this may further broaden the possibility of developing spectrum-based plant diagnoses for crop production and breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FTIR spectroscopy enables high-throughput measurements [ 53 , 54 ], suggesting that it can be used for chemo-typing heat-stress responses in crop breeding programs. Easier setup of FTIR spectroscopic facilities in comparison to that of other metabolomic platforms may also be beneficial for applying this technology to field metabolome studies [ 55 , 56 ]. Recently, FTIR-based remote sensing technologies have emerged as a new tool for monitoring the surface properties of land [ 15 , 57 ], and this may further broaden the possibility of developing spectrum-based plant diagnoses for crop production and breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the contradictory findings found in the literature [ 39 ], several studies have reported that Ficus carica L. extracts are endowed with potential health benefits against obesity-associated metabolic disorders and diabetes, but their mechanism of action is still debated [ 14 , 19 ] and the compounds responsible for the bioactivities have not yet been identified. Moreover, the plant metabolome is strongly affected by a number of biotic and abiotic factors, including seasonal variation [ 27 ]. The fluctuation in plant metabolome can be consequently reflected in their biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…The spectra were manually phased and baseline corrected and calibrated to the internal standard trimethyl silyl propionic acid sodium salt (TMSP) at δ 0.0 using Mestrenova software (Mestrelab Research, Spain). The analysis of 1 H-NMR profiles of extracts was performed based on an in-house library and in comparison with the literature [ 26 , 27 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The samples were dried at 40˚C and powdered using an electrical grinder (IKA, A11 basic, Merck, Italy). Plants extracts were prepared according to Mandrone et al [43] with slight modifications. Briefly, thirty mg of each sample were extracted with 1 mL of mixture (1:1) of phosphate buffer (90 mM; pH 6.0) in H 2 O-d2 (containing 0.01% TMSP) and MeOH-d4 by ultrasonication (TransSonic TP 690, Elma, Germany) for 20 minutes.…”
Section: Metabolomic Analysismentioning
confidence: 99%